African city diplomacy in global climate mobility debates - Stürner-Siovitz, Janina; Morthorst, Lasse Juhl (Global Networks - A Journal of Transnational Affairs, 2024)
While researchers have paid growing attention to transnational city engagement in both the policy fields of migration and climate change, there is a dearth of studies exploring how cities claim agency and start acting in emerging global climate mobility debates. Moreover, city diplomacy research tends to focus predominantly on city actors from the global North. We aim to address this research bias and advance academic debates by exploring African city diplomacy in global climate mobility debates. Specifically, we examine the question: How do African cities claim recognition as relevant actors in global dialogues on climate mobility, and what kind of action do they take? To find answers, we draw on a role theory framework analysing empirical research undertaken within an international, interdisciplinary research project.
CRIS-Team Scopus Importer:2024-03-22
Keywords: Africa; city diplomacy; climate mobility; role theory; transnationalism